Safety and efficacy of STI-571 (imatinib mesylate) in patients with bcr/abl-positive chronic myelogenous leukemia (CML) after autologous peripheral blood stem cell transplantation (PBSCT) - Fischer, Thomas; Reifenrath, C.; Hess, G. R.; Corsetti, M. T.; Kreil, Sebastian; Beck, J.; Meinhardt, P.; Beltrami, G.; Schuch, B.; Gschaidmeier, Harald; Hehlmann, Rüdiger; Hochhaus, Andreas; et al. (Leukemia, 2002)
We examined safety and efficacy of STI-571 in 24 bcr/abl-positive patients with CML post PBSCT. At start of STI-571 therapy, nine patients presented in blast crisis (BC) or in accelerated phase (AP), and 15 in chronic phase (CP). Patients were evaluated for hematologic, cytogenetic and molecular response, survival and toxicity. In general, STI-571 was well tolerated in this heavily pretreated group of patients with a non-hematologic and hematologic toxicity profile similar to that observed in a previous phase I trial at comparable doses. Five of nine patients with CML in transformation (AP, BC) were evaluable for hematologic response. Two of five patients had transient reductions in WBC and blasts, and three patients achieved a sustained hematologic response (>4 weeks). Cytogenetic analysis in these patients revealed numerical and/or structural responses. In CML chronic phase, STI-571 induced complete hematologic responses in all patients and major cytogenetic responses in 61% of patients with a complete cytogenetic response rate of 46%. This report indicates that STI-571 is a safe and effective drug in heavily pretreated patients. No apparent additional side-effects were noted in this patient cohort. The high rate of complete hematologic and complete cytogenetic responses in CP patients is remarkable, as intensive treatment approaches plus IFN-alpha failed to be efficient in achieving long-term stabilization of CML in this patient cohort.
Gesehen am 17.05.2022